2002
DOI: 10.1002/rsa.10029
|View full text |Cite
|
Sign up to set email alerts
|

Bond percolation critical probability bounds for three Archimedean lattices

Abstract: ABSTRACT:Rigorous bounds for the bond percolation critical probability are determined for three Archimedean lattices: .7385 Ͻ p c ((3, 12 2 ) bond) Ͻ .7449, .6430 Ͻ p c ((4, 6, 12) bond) Ͻ .7376, .6281 Ͻ p c ((4, 8 2 ) bond) Ͻ .7201. Consequently, the bond percolation critical probability of the (3, 12 2 ) lattice is strictly larger than those of the other ten Archimedean lattices. Thus, the (3, 12 2 ) bond percolation critical probability is possibly the largest of any vertex-transitive graph with bond p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
2
13
1
1
Order By: Relevance
“…. , and Wierman [16] established rigorous bounds of (0.738598, 0.744900) using the substitution method. Using the symmetry reduction technique, we tightened this bound to (0.739399, 0.741757) in May and Wierman [9].…”
Section: Results For the (3 12 2 ) Bond Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…. , and Wierman [16] established rigorous bounds of (0.738598, 0.744900) using the substitution method. Using the symmetry reduction technique, we tightened this bound to (0.739399, 0.741757) in May and Wierman [9].…”
Section: Results For the (3 12 2 ) Bond Modelmentioning
confidence: 99%
“…We define an up-set of n to be a subset U of n such that, if π 1 ∈ U and π 1 < π 2 , then π 2 ∈ U . If P G p (π ) and P H p c (π ) are probability measures on n , then P G p is stochastically no greater than P H p c (denoted [16,17].…”
Section: The Substitution Methodsmentioning
confidence: 99%
“…The remarkable fact that allows exact bond percolation threshold values to be obtained is that it is possible to choose the parameters p and q so that the two probability measures are exactly equal. (Note that in cases with more boundary vertices, where the probability measures cannot be made equal, the concept of stochastic ordering of probability measures may be used to determine mathematically rigorous bounds for percolation thresholds, using the substitution method [12,13,22,24,25,26,27].) By the duality relationship between G and G * , we have that for each configuration of open and closed edges, the following five statements hold: While these statements are intuitively clear by drawing diagrams, the proofs of these statements rely on duality.…”
Section: Reduction To a Single Equationmentioning
confidence: 99%
“…Suding and Ziff presented precise thresholds for site percolation on eight Archimedean lattices determined by the hullwalk gradient-percolation simulation method [26]. Rigorous bounds for the bond percolation critical probability are determined for three Archimedean lattices by Wierman [27]. In addition, Scullard and Ziff showed that the exact determination of the bond percolation threshold for the Martini lattice can be used to provide approximations to the Kagome and (3, 12 2 ) lattices [28].…”
Section: Introductionmentioning
confidence: 99%